Slot development using the controlled blasting in the ore body "Borska reka" - Vojinović Ivica; Svrkota Igor; Stojanović Miloš; Šabaz Dragan; Rajković Radmilo (Mining and Metallurgy Engineering Bor)
The occurrence of deviations in the drilling of long blast holes can negatively impact the quality of blasting and safety of personnel and pillars in the room and pillar mining methods. The application of controlled blasting through a two-step blasting process for creating a compensation chamber (slot) is presented due to the occurrence of blast hole deviations. Initiation sequences of holes in the two-step blasting process were determined by surveying the holes and simulating blasting in the Datamine Aegis software. Blasting the lower and upper parts of the slot created a free space of approximately 840 m³ with an approximate specific explosive consumption of 2.25 kg/m³